2007
DOI: 10.1007/s00198-007-0456-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D depletion among subjects seeking advice on osteoporosis: a five-year cross-sectional study with public health implications

Abstract: The prevalence of vitamin D depletion in patients seeking advice for osteoporosis is high and did not change over the 5 years of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 51 publications
4
18
1
3
Order By: Relevance
“…This finding is not surprising as a couple studies have established the association between vitamin D deficiency and osteoporosis [11,14]. However, if patients with an established diagnosis of osteoporosis were treated following the national guidelines, we should find a lower prevalence of vitamin D deficiency [3].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This finding is not surprising as a couple studies have established the association between vitamin D deficiency and osteoporosis [11,14]. However, if patients with an established diagnosis of osteoporosis were treated following the national guidelines, we should find a lower prevalence of vitamin D deficiency [3].…”
Section: Discussionmentioning
confidence: 69%
“…We did not identify any sex-related prevalence of vitamin D deficiency. The reported association between sex and vitamin D varies, with some studies describing higher rates in men [3,14] and others in women [8,21]. Bogunovic et al [3], in a prevalence study, and Guardia et al [14], reported male sex as a risk factor for vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of vitamin D deficiency in this study was high and comparable with that of the general population (Chapuy et al, 1997;Guardia et al, 2008), with 28% of enrolled participants presenting with mild deficiency [16-19 ng/ mL serum 25(OH)D level]. 25OHD values lower than 16 ng/mL have been shown to have a drastic effect on PTH levels (Carnevale et al, 2010).…”
Section: Discussionmentioning
confidence: 76%
“…Thirty-eight out of the 400 children involved in the study were suffering from with vitamin D deficiency was significantly higher among children with black skin than children with fair skin [12]. Although it is a protective factor against sunburn, skin pigmentation is a major cause of vitamin D deficiency in children.…”
Section: Prevalence Of Hypovitaminosismentioning
confidence: 99%